2019
DOI: 10.1039/c9re00222g
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and reactor modeling of the conversion of n-pentane using HZSM-5 catalysts with different Si/Al ratios

Abstract: The production of olefins and aromatics from n-pentane using two ZSM-5 catalysts is faithfully predicted by a versatile kinetic model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 49 publications
0
7
0
1
Order By: Relevance
“…At the studied conditions, olefins are the main products but significant yields of C 5+ hydrocarbons (nonaromatics) are also predicted. In a previous work, the valorization of these byproducts were studied by the catalytic cracking of n -pentane as the model compound . This constitutes a possibility for the intensification of olefin production in a secondary process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the studied conditions, olefins are the main products but significant yields of C 5+ hydrocarbons (nonaromatics) are also predicted. In a previous work, the valorization of these byproducts were studied by the catalytic cracking of n -pentane as the model compound . This constitutes a possibility for the intensification of olefin production in a secondary process.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous work, the valorization of these byproducts were studied by the catalytic cracking of n-pentane as the model compound. 46 This constitutes a possibility for the intensification of olefin production in a secondary process. Several simulations of the reactor−regenerator system using the CZ140 catalyst were performed in a wider range of operating conditions in order to provide an operation map of the yields of these two lumps.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] Cordero-Lanzac et al found ideal conditions using kinetics and reactor modeling for the catalytic transformation of n-C5 (550°C and 3.5 g-cat h mol À 1 ) in maximizing BTX yield and selectivity (yield and selectivity of 53 %) over ZSM-5 (Si/Al 2 = 30). [18] Wannapakdee et al researched n-pentane aromatization with conversion 40 % and BTEX selectivity 45 %, using HZSM-5 nanosheets improved with Ga. [19] Experimental and density functional theory (DFT) data also confirmed the behavior of the hierarchical Ga incorporated zeolite nanosheets.…”
Section: Introductionmentioning
confidence: 96%
“…Parafinen interes komertziala mugatua da, erreaktibotasun eta oktano-indize txikia dutelako. Gaur egun, C 4 -C 7 parafinen cracking katalitikoa ikertzen ari da, olefinak selektiboki lortzeko prozesu espezifikoa garatzeko asmoz [45].…”
Section: Beste Prozesuakunclassified